THE INFLUENCE OF ECO-LABEL ON ENVIRONMENTAL CONCERN OF LOCAL SKINCARE BRAND CONSUMERS IN ACEH WITH PRODUCT ATTRIBUTES AND PERCEIVED OF EFFECTIVENESS AS MEDIATION - Fadhila, Jihan; Halim, Hendra; Sulthan DM, Burhanis (International Journal of Kita Kreatif, 2024)
The purpose of this study is to examine how consumers of local skincare brands in Aceh are affected by eco-labels regarding their environmental concerns, using product features and perceived efficacy as a moderator. This study employed primary data for its analysis. This research applies a quantitative method with a population of local skincare brand users in Aceh. Using purposive and non-probability sampling strategies, 104 respondents made up the overall sample size. With the use of SPSS, mediation regression is a data analysis approach. The study's findings demonstrate that environmental concern is positively impacted by the eco-label variable. The impact of eco-labels on environmental concern is partially mediated by perceived efficacy and product attribute factors.